Study on the effect of ascorbic acid on the biosynthesis of pigment and citrinin in red yeast rice based on comparative transcriptomics - Jiang, Zhilin; Duan, Yunxun; Yin, Qianqian; Zhang, Jing; Chen, Jing; Lan, Jingsha; Xiao, Chen; Tang, Xian; Wang, Xinhui; Zuo, Yong (Frontiers in Microbiology, 2024)
Pigment is one of the most important metabolites in red yeast rice.However, citrinin may accumulate and bring quality security issue. In the present study, the effect of ascorbic acid (EAA) on the pigment and citrinin was studied, and the metabolic mechanism was discussed by comparative transcriptomic. The introduction of EAA increased the pigment by 58.2% and decreased citrinin by 65.4%.The acid protease activity, DPPH scavenging rate and total reducing ability also increased by 18.7%, 9.0% and 26.7%, respectively. Additionally, a total of 791 differentially expressed genes were identified, and 79 metabolic pathways were annotated, among which carbon metabolism, amino acid metabolism and fatty acid metabolism were closely related to the biosynthesis of pigment and citrinin. Ethanol dehydrogenase (M pigC), oxidoreductase (M pigE), reductase (M pigH) and monooxygenase (M pigN) may be related to the increase of pigment. ctnC and pksCT were contributed to the decline of citrinin.